Rozwiąż układ równań metodą przeciwnych współczynników:

2x-3y=7
3x-5y=11


Odpowiedź :

2x-3y=7/ ×(-3)
3x-5y=11 / ×2

-6x+ 9y= -21
6x- 10y= 22

-y=1
y=-1

2x-3y=7
2x- 3(-1)= 7
2x+3=7
2x=4/÷2
x=2

x=2
y=-1
2x-3y=7 | *(-3)
3x-5y=11 | *2

-6x+9y=-21
+ 6x-10y=22

-6x+6x+9y-10y=-21+22
-y=1
y=-1
podstawiamy "y" do pierwszego równania
2x-3*(-1)=7
2x+3=7
2x=4
x=2

x=2
y=-1
2x - 3y = 7 /*(-3)
3x - 5y = 11 / *2

-6x + 9y = -21
6x - 10y = 22

-y=1 / :(-1)
y=-1

2x - 3*(-1 )= 7
2x+3 = 7
2x = 4 /:2
x = 2

x=2
y=-1